2017
DOI: 10.1016/j.jad.2016.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala and dlPFC abnormalities, with aberrant connectivity and habituation in response to emotional stimuli in females with BPD

Abstract: dlPFC abnormalities, with aberrant connectivity and habituation in response to emotional stimuli in females with BPD, Journal of Affective Disorders, http://dx.doi.org/10.1016Disorders, http://dx.doi.org/10. /j.jad.2016 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…All four studies (Dudas et al, ; Ille et al, ; Schienle, Haas‐Krammer, Schoggl, Kapfhammer, & Ille, ; Schienle et al, ) employed a case‐controlled design and utilized multi‐item measures of self‐disgust (the QASD). Three of these studies (Dudas et al, ; Schienle et al, ; Schienle et al, ) also demonstrated differential patterns of activation in the amygdala brain regions in the client group relative to a control group, and an increased sensitivity to facial expressions of disgust in others. Schienle et al () postulated that the latter findings may have been due to life experiences that have shaped predictions of rejection, thus sensitizing participants to expressions of disgust from others.…”
Section: Resultsmentioning
confidence: 99%
“…All four studies (Dudas et al, ; Ille et al, ; Schienle, Haas‐Krammer, Schoggl, Kapfhammer, & Ille, ; Schienle et al, ) employed a case‐controlled design and utilized multi‐item measures of self‐disgust (the QASD). Three of these studies (Dudas et al, ; Schienle et al, ; Schienle et al, ) also demonstrated differential patterns of activation in the amygdala brain regions in the client group relative to a control group, and an increased sensitivity to facial expressions of disgust in others. Schienle et al () postulated that the latter findings may have been due to life experiences that have shaped predictions of rejection, thus sensitizing participants to expressions of disgust from others.…”
Section: Resultsmentioning
confidence: 99%
“…This distinction in the direction of connectivity aberrancy separates FND patients from general disorders of mood and anxiety. Interestingly, increased functional connectivity between amygdala and dorsolateral PFC is found in patients with borderline personality disorder ( Dudas et al, 2017 ), a group that is often characterized by dissociative responses to traumatic emotional events ( Vermetten and Spiegel, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, because non-contact measurement technology needs to be verified under physiological change in order to apply the various environments or industries. Many previous studies reported that autonomic nervous system (ANS) has been found to be closely connected with the pupillary rhythms, exhibiting repeated contraction and expansion via the sphincter and dilator muscles (Bonvallet and Zbrozyna, 1963 ; Loewenfeld and Lowenstein, 1993 ; Steinhauer et al, 2000 ; Verney et al, 2001 ; Siegle et al, 2004 ), and the emotional stimuli presented in this study such as arousal, relaxation, positive, and negative are closely related to the ANS (Yang et al, 2007 ; Levenson, 2014 ; Dudas et al, 2017 ). Also, changes in pupillary rhythms have been related to neural activity in the dorsolateral prefrontal cortex (DLPFC) (Siegle et al, 2011 ), and this region is known to associate with a more cognitive effort to regulate emotions for affective event (Ochsner et al, 2004 ; Vanderhasselt et al, 2014 ; Dudas et al, 2017 ).…”
Section: Discussionmentioning
confidence: 80%